WORKPLACE OSTRACISM IN THE SELECTED SERVICE SECTOR ORGANIZATIONS IN CHHATTISGARH: IMPLICATIONS FOR EMPLOYEE WELL-BEING AND ORGANIZATIONAL PERFORMANCE - Sharma, Akriti; Abdullah, Hamid; Bano, Afrin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of workplace ostracism on employee well-being, performance, engagement, and withdrawal intentions in service sector organizations in Chhattisgarh. Through a descriptive research design, data was collected from 300 employees across various industries including finance, banking, transportation, and BPOs. The study reveals that workplace ostracism significantly reduces employees’ psychological well-being, job satisfaction, and productivity, while increasing absenteeism and turnover intentions. Furthermore, perceived organizational support was found to moderate the negative effects of ostracism, helping employees better cope with exclusionary behaviors. The findings underscore the importance of raising awareness about ostracism, fostering employee engagement, and creating inclusive work environments. The study concludes with practical recommendations for organizations to address ostracism through training, leadership development, peer mentoring, and promoting psychological safety, aiming to improve both individual and organizational outcomes.